Media in Pink and Blue: Gender Identity Performance in Twitch Gaming Communities - Vawter, Laura (Pedagogika Społeczna Nova, 2025)
The female and male “gamer” identity heavily influence the language actions of Multilinguals within the gaming community. Multilingual performance of the gamer identity can maintain gender stereotypes. These stereotypes are also reinforced by community members participating in streams of multilingual gamers. Community members, gamers, and streamers in EU-based gaming communities often reinforce the cultural gender norms and confine gender performance to males and females. Violation of this strict gender performance can correlate to bullying and sexual harassment by members of the gaming community. Through Computer-Mediated Dialogue Analysis of Twitch streams, we explore the language actions of multilinguals in these spaces. We examine the derogatory language practices found in multilingual gaming communities, as well as the language practices that challenge cultural gender norms through the examination of female-centered slurs and male-centered colloquiums. The argument is presented that gaming communities, and their members, have the capacity to both reinforce and diminish gender stereotypes.